CODE SWITCHING USED IN FATHIA IZZATI'S YOUTUBE VIDEOS - Saputra, Roni; Fadilah, Eka; Kurniawan, Yulius (Seminar Nasional Ilmu Terapan, 2023)
This research aims to find out what types of code switching are used and the reasons for using code switching by YouTuber Fathia Izzati in her conversations based on Hoffman's theory. This research uses a qualitative descriptive method, because the object of this research is taken from YouTube videos. To get data there are several steps taken, namely watching and listening to videos, making transcriptions of videos, select the utterances consisting of code switching. The main theory used to analyze the data focuses only on Hoffman's theory (1991) to analyze the types of code switching and the reasons for using code switching. The results of this analysis show that all types of code-switching are found in Fathia Izzati's utterances namely, Intra-sentential switching, Inter-sentential switching, and Tags-switching. The results of this analysis show that this study can find all types of code switching in Fathia Izzati's utterances. On the other hand, for the reasons for the use of code switching based on Hoffman's theory, the researcher found that of the 7 existing reasons, only 5 reasons for the use of code switching were found in the three selected Fathia Izzati videos, that is Talking about particular topic, be emphatic about something, Interjection, Repetition used for clarification, Clarifying the speech content for the interlocutor. The purpose of using code switching has been explained in the YouTube Channel Fathia Izzati video.